Penerapan Pendidikan Karakter Dalam Mengatasi Kenakalan Remaja - Kahfi, Muhammad; Ishak Syairozi (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
The purpose of this study is to examine how the implementation of character education can help address juvenile delinquency at MA Al-Ihsan Pondok Gede Jatiwaringin. The increasing phenomenon of juvenile delinquency is the background of this research. This phenomenon can disrupt learning and damage students' character, such as truancy, fighting, violations of school rules, and other deviant behaviors. This research employs a descriptive qualitative study using observation, interviews, and documentation as data collection methods. The results of the study indicate that MA Al-Ihsan has implemented character education through various methods, such as integrating character values into learning activities, religious activities, teacher examples, and school practices and culture. Discipline, responsibility, honesty, and social concern are the values emphasized. However, there are still issues. These include a lack of consistency in implementation among teachers, the influence of external environments, and limitations in evaluating character programs. In general, character education has proven to play an important role in shaping students' morality and reducing deviant behavior. This study also suggests that schools, families, and communities should collaborate more, and character education programs should be evaluated regularly. Keywords: Character education, juvenile delinquency, moral development, discipline, responsibility, Islamic education, character approach.